The relationship between artificial intelligence anxiety and unemployment anxiety among university students. - Uçar, Mehmet; Çapuk, Hüseyin; Yiğit, Muhammet Faruk (Work, 2025)
Background: The idea that people will lose their jobs because of robots with artificial intelligence is one of the biggest recent concerns about artificial intelligence technology. There are predictions that unemployment will increase with the introduction of robots into the business sector, and due to artificial intelligence, automation in the production sector will make work completed by robots more practical than the efforts accomplished by humans. Objective: This study aimed to assess the correlation between artificial intelligence anxiety and the level of unemployment anxiety among university students. Methods: As a cross-sectional and descriptive study, the population comprised of 10,682 university students actively enrolled at a university. While the minimum sample size was calculated as 371 students, the research included 476 students as participants. The study used the 'Personal Information Form', 'Artificial Intelligence Anxiety Scale', and 'Unemployment Anxiety Scale' as data collection tools. Results: The demographic information of the participants follows: 50.4% were male, 33.8% were freshmen, and 96.2% were single. The total score averages for the Artificial Intelligence Anxiety Scale and Unemployment Anxiety Scale are 56.00 ± 15.51 and 53.52 ± 11.55, respectively. A statistically significant difference between the participants' score averages on the Artificial Intelligence Anxiety Scale and the Unemployment Anxiety Scale was identified for gender, major/college, trust in technology, and use of artificial intelligence (p < 0.05). There was a moderately positive relationship between artificial intelligence anxiety and unemployment anxiety level total score averages (p < 0.01). Conclusions: There were high scores among participants for artificial intelligence anxiety and unemployment anxiety.